2007
DOI: 10.1089/neu.2007.0342
|View full text |Cite
|
Sign up to set email alerts
|

Early Excision and Late Excision of Heterotopic Ossification after Traumatic Brain Injury Are Equivalent: A Systematic Review of the Literature

Abstract: Heterotopic ossification (HO) is a common complication in patients with coma after brain injury. As the optimal timing of surgical resection is still controversial and unclear, a review of the literature was performed in order to determine the impact of early operation on recurrence rate and joint mobility. We identified all types of studies dealing with surgical excision of HO in patients after head injury in major medical and publishers' databases. Publication bias and statistical heterogeneity were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 42 publications
2
49
0
4
Order By: Relevance
“…These treatments options include nonsteroidal antiinflammatory drugs (NSAIDs) and radiotherapy (often in combination), although adverse effects have been associated with their use [8,9,20,57]. Surgical excision of HO is another therapeutic option, although recurrence of HO at the surgical site may ensue [10,13,65]. Furthermore, contemporary treatment options are not engineered specifically to impede the biological mechanisms responsible for the production of bone in soft tissue.…”
Section: Introductionmentioning
confidence: 99%
“…These treatments options include nonsteroidal antiinflammatory drugs (NSAIDs) and radiotherapy (often in combination), although adverse effects have been associated with their use [8,9,20,57]. Surgical excision of HO is another therapeutic option, although recurrence of HO at the surgical site may ensue [10,13,65]. Furthermore, contemporary treatment options are not engineered specifically to impede the biological mechanisms responsible for the production of bone in soft tissue.…”
Section: Introductionmentioning
confidence: 99%
“…HO in TBI cases usually occurs on hemiplegic limbs, whereas occurring in the neurologically noninvolved side is rare [7][8][9][10]. Chalidis et al [3] found that altering the natural course of HO is difficult once it has started [3,11]. Therefore, prevention should be emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Among the population of individuals with traumatic brain injury (TBI), the estimated prevalence of clinical heterotopic ossification (HO) is more than 20 percent [1], which can severely restrict range of motion (ROM) in the involved joints [1][2][3]. The effectiveness of pharmacological prophylaxis has not been irrefutably proven, and prophylactic irradiation runs a potential risk of malignancy [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…adversely affecting the quality of life of already physically compromised patients with TBI [2,[6][7][8][9][10] . Pharmacotherapy to date has not proven to be successful once NHO has formed [11,12] , thus surgical removal remains the only treatment option for NHO but is extremely invasive and not always possible for all TBI patients [13] .…”
Section: Introductionmentioning
confidence: 99%